Incorporating gendered landscapes into physically-based models via Participatory 3-D Mapping. [Abstract only] - Baker, Tracy; Debevec, Liza; Abebe, Yenenesh; Cullen, Beth (2014)
Biophysical scientists struggle integrating "gendered" water uses into models, with the latter necessarily based on physical laws describing water movement through the hydrological cycle. We typically assess watershed hydrological response to land management in terms of biophysical response. We may then loosely couple this to socio-economic variables. Results often present an incomplete picture of people‘s needs. Traditional methods used to describe socio-economic aspects of communities are not well-suited for inclusion directly into biophysical models. Scenario development supported by socio-economic data may be employed to account for agricultural productivity, land management, and water allocation within biophysical models. To address this, a simple methodology is being tested to incorporate gendered perceptions into biophysical assessments of water resources. A small watershed (Jeldu, Ethiopia) is used as a case study to generate gender differentiated three-dimensional landscape representations that are then georeferenced into ArcGIS. A spatial analysis and interpretation of men‘s versus women‘s identification and use of water resources is carried out, and the land use maps are used as the principal land use input for the Soil and Water Assessment Tool (SWAT).